2020
DOI: 10.1109/access.2020.3020924
|View full text |Cite
|
Sign up to set email alerts
|

Extracting Dense and Connected Communities in Dual Networks: An Alignment Based Algorithm

Abstract: Networks-based models have been used to represent and analyse datasets in many fields such as computational biology, medical informatics and social networks. Nevertheless, it has been recently shown that, in their standard form, they are unable to capture some aspects of the investigated scenarios. Thus, more complex and enriched models, such as heterogeneous networks or dual networks, have been proposed. We focus on the latter model, which consists of a pair of networks having the same nodes but different edg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…4 Architecture of the Dual Network Analyser tool
Fig. 5 Alignment Example: the Algorithm receives as input two networks and a set of similarity relationship among nodes of the networks (dashed lines) [ 18 ]
Fig. 6 First, the algorithm builds the nodes of the heterogeneous alignment graph.
…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 Architecture of the Dual Network Analyser tool
Fig. 5 Alignment Example: the Algorithm receives as input two networks and a set of similarity relationship among nodes of the networks (dashed lines) [ 18 ]
Fig. 6 First, the algorithm builds the nodes of the heterogeneous alignment graph.
…”
Section: Introductionmentioning
confidence: 99%
“… Alignment Example: the Algorithm receives as input two networks and a set of similarity relationship among nodes of the networks (dashed lines) [ 18 ] …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance (Guzzi et al. 2020 ), showed that DCS may suggest missing links in social networks, capture similar interests among authors in a co-authorships dual network, where physical network represents co-authors and the conceptual network is used to model topics shared.…”
Section: Introductionmentioning
confidence: 99%